1996
DOI: 10.1095/biolreprod55.6.1305
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of an Estrogen-Dependent Porcine Oviductal Secretory Glycoprotein1

Abstract: A family of estrogen-dependent porcine oviductal secretory glycoproteins (POSPs) that exhibit structural similarities are synthesized and secreted into the oviductal lumen at proestrus, estrus, and metestrus. The objectives of this study were to clone the POSP cDNA, obtain the full-length cDNA and protein sequence, examine tissue specificity and species distribution, characterize its regulation, and establish its identity by comparison to other known protein, RNA, or DNA sequences. A full-length cDNA of 2022 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 53 publications
5
49
1
Order By: Relevance
“…In particular, the inverse relationship between protein concentrations and the concentrations of P 4 is consistent with the findings of Buhi et al [8] who showed that porcine oviductal tissue during estrus has the highest levels of de novo protein synthesis and secretion. The temporal changes in pOSP mRNA expression and the secreted pOSP proteins in relation to the time of ovulation are consistent with evidence that pOSP expression is E 2 -dependent [11]. Thus, as the steroid milieu of the oviduct became progesterone dominated by day 2 after ovulation, a major decline in both pOSP mRNA expression and pOSPs in oviduct fluid was observed.…”
Section: Oviduct Flushingssupporting
confidence: 82%
See 2 more Smart Citations
“…In particular, the inverse relationship between protein concentrations and the concentrations of P 4 is consistent with the findings of Buhi et al [8] who showed that porcine oviductal tissue during estrus has the highest levels of de novo protein synthesis and secretion. The temporal changes in pOSP mRNA expression and the secreted pOSP proteins in relation to the time of ovulation are consistent with evidence that pOSP expression is E 2 -dependent [11]. Thus, as the steroid milieu of the oviduct became progesterone dominated by day 2 after ovulation, a major decline in both pOSP mRNA expression and pOSPs in oviduct fluid was observed.…”
Section: Oviduct Flushingssupporting
confidence: 82%
“…Although previous studies have characterized IGF-I concentrations [29] and pOSP protein and mRNA abundance [11] during the estrous cycle, neither reported changes during the critical periovulatory period. Furthermore, because we have shown that the interval between the onset of estrus and the time of ovulation is highly variable in gilts, we believed it was critical to use the moment of ovulation as a critical reference point in these studies.…”
Section: Oviduct Flushingsmentioning
confidence: 87%
See 1 more Smart Citation
“…cycle, (ii) nucleotide and amino acid sequences of OGP are highly conserved between species (29) (Table S3), which agrees with the crossed action of porcine and bovine fluids, and (iii) OGP possesses heparin-binding consensus sequences (29) and heparin-binding sites (30), which would explain why heparin in the incubation medium stabilizes the hardening effect. To demonstrate the involvement of OGP in ZP modifications and its detachment in a medium lacking heparin, different experiments were performed.…”
Section: Oviduct-specific Glycoprotein Seems To Be Responsible For Thesupporting
confidence: 57%
“…So it is necessary to study the function of CTP rabbit oviductin in the development of early embryo. The homology comparisons also showed that there were 40-50% smilarities between rabbit oviductin and some enzymes of chitinase gene family, but the oviductins showed no chitinase activity [14]. In recent years, few researches concerning the roles of oviductins in the development of early embryo were reported [15], [16].…”
Section: Discussionmentioning
confidence: 92%